Pengaruh Sikap Wajib Pajak, Kesadaran Wajib Pajak, Dan Pengetahuan Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi Pada Pelaku Ekonomi Kreatif Sub Sektor Fashion Di Kota Batu - Merinda Yuanita Yustikasari; Jeni Susyanti; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis study aims to determine the effect of partial and simultaneous variables of the attitude of taxpayers, taxpayers awareness, and tax knowledge on individual taxpayer compliance on the creative economy actors in the fashion sub sector in Batu City. The data analysis technique used in this study is multiple linier regression analysis. The sample size used was 82 respondents with a total population of 468 SMEs in the fashion sub sector in Batu City registered at a Batu City Cooperative, Micro Business and Trade Office. The results of this study indicate that partially the attitude of taxpayer attitudes has a positive and significant effect on taxpayer compliance. Awareness of taxpayers no significant effect on taxpayer compliance. Knowledge of taxation has a positive and significant effect on taxpayer compliance. Simultaneously variable attitude of taxpayer, taxpayer awareness, and tax knowledge have a positive and significant effect on taxpayer compliance of individual taxpayers of the creative economy actors in the fashion sub sector in Batu City.  Keywords: Attitudes of taxpayers, taxpayer awareness, tax knowledge, and taxpayer compliance